Preparation and Characterization of Hydrogels Based on Homopolymeric Fractions of Sodium Alginate and Pnipaam - Encina-Rojas, M; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Leal-Rifo, D (2013)
Sin Editorial Disponible